Acne treatment efficacy of intense pulsed light photodynamic therapy with topical licochalcone A, l-carnitine, and decanediol: A spilt-face, double-blind, randomized controlled trial - Rungsima Wanitphakdeedecha (2020)
© 2019 Wiley Periodicals, Inc. Background: Depending on disease severity, standard acne treatments can vary from topical to systemic therapy. However, poor compliance caused by adverse events and antibiotic resistance is a major cause of treatment failure. Aims: To determine the effectiveness of photodynamic therapy (PDT) with intense pulsed light (IPL) in the treatment of acne when combined with a cream containing licochalcone A, L-carnitine and decanediol (so-called, ‘active formulation’) versus PDT alone. Patients/Methods: Twenty-nine volunteers, aged 21-39 years (26 women and 3 men, mean age 29.41 ± 5.24 years), with mild to severe facial acne, were enrolled. Each subject’s face sides were randomized in a split-face manner to either receive PDT (IPL with a 400-720 nm cut-off filter, at 4 sessions with two-week intervals) combined with the active formulation cream twice daily for 10 weeks on one face side; or PDT and the vehicle cream on the other side, with the same treatment protocol. Reduction in acne quantity, melanin index and erythema index were assessed 2 weeks after the second treatment (day 28), 1 week after the fourth treatment (day 49), and 1 month after the fourth treatment (day 70). Results: Compared to baseline, patients in the active formulation group demonstrated a faster onset of reduction in the number of lesions at 2 weeks after the second treatment (p=0.010 for inflammatory acne and p=0.001 for non-inflammatory acne). A significantly greater reduction in lesion count was observed in the active formulation group compared with the vehicle group at all timepoints of evaluation for noninflammatory acne (day 28, day 49, and day 70; p=0.003, 0.005 and 0.002 respectively), and at 1 month after the fourth treatment for inflammatory acne (p=0.036). Compared to the vehicle group, the melanin index of the active formulation group decreased significantly at 1 month after the fourth treatment (p=0.015). Conclusion: PDT is more effective in treating acne when combined with a topical cream containing licochalcone A, L-carnitine and decanediol, than PDT alone. Significant acne reduction and improvements in post-inflammatory hyperpigmentation were observed, which offers acne patients a better therapeutic option. It is a safe and effective combination treatment for patients with moderate and severe acne.